2017
DOI: 10.3892/or.2017.5744
|View full text |Cite
|
Sign up to set email alerts
|

Klotho suppresses tumor progression via inhibiting IGF-1R signaling in T-cell lymphoma

Abstract: Klotho is a transmembrane protein and acts as an upstream modulator of insulin-like growth factor-1 receptor (IGF-1R) signaling, which was indicated to be involved in the pathogenesis of solid cancer and hematological malignancies, including T‑cell lymphoma. Although Klotho was recently identified as a tumor suppressor in several types of human malignancies, the potential role of Klotho in T‑cell lymphoma has not been reported. In the present study, we investigated the expression level and the molecular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…3E). Prior studies have demonstrated that klotho suppresses the growth of various cancer cells by inhibiting several pathways implicated in the pathogenesis of PKD, including Wnt/␤-catenin and insulin-like growth factor 1 signals (34,45,49,50). Additionally, klotho has been demonstrated to increase intracellular Ca 2ϩ in tubular epithelial cells (6,23,44), an action that has been shown to suppress the mitogenic response to cAMP in cystic epithelial cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…3E). Prior studies have demonstrated that klotho suppresses the growth of various cancer cells by inhibiting several pathways implicated in the pathogenesis of PKD, including Wnt/␤-catenin and insulin-like growth factor 1 signals (34,45,49,50). Additionally, klotho has been demonstrated to increase intracellular Ca 2ϩ in tubular epithelial cells (6,23,44), an action that has been shown to suppress the mitogenic response to cAMP in cystic epithelial cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was scored by two independent observers who were blinded to the patients' clinical data. The scoring system for grading the level of YAP was reported previously [22]. The expression level was evaluated by immunohistochemistry (IHC) score calculated by multiplying a proportion score and intensity score.…”
Section: Immunohistochemistry and Hematoxylin-eosin Stainingmentioning
confidence: 99%
“…The scores were independently evaluated by two observers. The criterion for determining the presence of klotho staining was 10%, as referenced in two studies [ 25 , 26 ]. The proportion score was determined as 0 (<10%), 1 (10–25%), 2 (26–50%), 3 (51–75%), or 4 (>75%) according to the percentages of positive staining areas in five representative high-power fields.…”
Section: Methodsmentioning
confidence: 99%